THE INFLUENCE OF TEACHER PEDAGOGIC COMPETENCE ON STUDENTS' CRITICAL THINKING ABILITY AT SMP NEGERI 7 TAMALATEA JENEPONTO REGENCY - Riska Cahyani; Nurul Haeriyah Ridwan; Ariadna Muliyati (International Conference on Social and Islamic Studies, 2021)
This study aims to determine 1) the pedagogic competence of teachersat SMP Negeri 7 Tamalatea, Jeneponto Regency. 2) The critical thinking ability ofstudents at SMP Negeri 7 Tamalatea, Jeneponto Regency. 3) The influence ofteacher pedagogic competence on students' critical thinking skills at SMP Negeri 7Tamalatea, Jeneponto Regency. This research is a quantitative research with expost facto research type, with a population of 240 students and 10 teachers. Thesample used was 50 with purposive sampling technique so that a sample of 40 students of class VIII and 10 teachers was obtained, quantitatively. Data collectiontechniques are questionnaires, observations and interviews. With researchinstruments, namely questionnaires, documentation. The data analysis techniqueused descriptive statistics. The research results obtained include: 1) The pedagogiccompetence of teachers at SMP Negeri 7 Tamalatea, Jeneponto Regency isincluded in the frequent category with an average score of 24 or 48% located in theinterval 49-54. 2) The critical thinking ability of students at SMP Negeri 7 Tamalatea,Jeneponto Regency is included in the frequent category with an average score of 31or 62% located in the interval 46-51. 3) The results of the significance test with hij-tobtained t count 0.81 = 0.278 t table when compared, namely 0.81>0.278, meaningthat there is a significant influence between teacher pedagogic competence onstudents' critical thinking skills at SMP Negeri 7 Tamalatea, Jeneponto Regency. Soit can be concluded that there is an effect of teacher pedagogical competence on thecritical thinking skills of students at SMP Negeri 7 Tamalatea, Jeneponto Regency by 94.5% which can be seen from the summary model test. The implication of thisresearch is that the principal should make training or seminars on teachercompetence that must be attended by teachers, in order to master teachercompetence, especially pedagogic competence in order to encourage students tohave critical thinking skills.